Pengelolaan Dana Zakat dalam Bentuk Beasiswa Pendidikan dengan Syarat Perekrutan Tenaga Kerja Pada Lembaga Amil Zakat (Laz Sukoharjo) - Zaid Abu Malik; Muhsan Syafaruddin (Departement of Mathematics Education, 2023)
The purpose of this study is to review, analyze, find out the mechanism and practice of managing zakat funds that are utilized in the form of educational scholarships (scholarship) with the condition of becoming a workforce or assistance at LAZ Sukoharjo, and knowing the legal basis in terms of the positive aspects of Indonesian law and Islamic law which become basis for implementing the program. The research method used is field research with a qualitative approach, the data presentation is descriptive, the data collection technique is observation, interviews. Based on the results of research in the field, it can be interpreted that the basis for the management of zakat funds used for educational scholarships is Indonesian positive law Law no. 23 of 2011 concerning the management of zakat, and Islamic law QS. At-Taubah (9) 60 which explains about mustahik receiving zakat. Management of zakat funds in the form of educational scholarships (scholarships) by institutions intended for workforce (volunteers) by involving students who provide scholarships with the aim of increasing the space for human resources at LAZ Sukoharjo, increasing relationships, mobilizing, and also increasing the benefits for others.